Efektifitas Layanan Bimbingan dan Konseling Untuk Mengatasi Masalah Menyontek dan Pengaruhnya terhadap Prestasi Belajar Siswa SMA Negeri 11 Ambon - Purwatib, Purwatib (Guidance and Counseling Study Program, Pattimura University, 2018)
The problem of cheating for learners is not something new in the world of school. When school programs begin to enter the stage of assessment, then there are also various behavior patterns of learners to prepare themselves to face a test or test. In fact, in schools such as SMA Negeri 11 Ambon there are some students of class X IPS do cheat behavior at the time of replication take place. The research was conducted in SMA Negeri 11 Ambon, the result of the research showed that there were differences of learners behavior, before and after the students got guidance and counseling service. Of the 40 respondents who originally cheated, after being given guidance almost all declared no and have abandoned the attitude of cheating.